Research on maintenance procedures of structural standard practices for civil aircraft - LIU Zhonghua; SHI Hongwei (Hangkong gongcheng jinzhan)
The content scope and data sources need to be clarified for developing the maintenance procedures of structural standard practices in the aircraft maintenance manual. By researching on airworthiness regulations，industry specifications and aircraft maintenance manuals of international mainstream civil aircraft，the main contents to covered by the maintenance procedures of structural standard practices in the aircraft maintenance manual are sum marized，including corrosion prevention，internal and external finishes，airframe drainage and sealing. Combined with the development experience of domestic civil aircrafts，the main data sources required for the development of structural standard practices' maintenance procedures are summed up，including aircraft design drawings/digital models，manufacture process specifications，supplier product data，maintenance task analysis data，technical reports and industry standards. By considering the requirements of airlines to use maintenance procedures to develop task cards，the characteristics of the structural standard practices' maintenance procedures for domestic civil aircrafts are formed. The results show that the maintenance procedures of structural standard practices developed according to the content scope and data sources given in this paper meet the needs of aircraft maintenance very well.